2008
DOI: 10.3748/wjg.14.7214
|View full text |Cite
|
Sign up to set email alerts
|

Transjugular intrahepatic portosystemic shunt-placement increases arginine/asymmetric dimethylarginine ratio in cirrhotic patients

Abstract: AIM:To analyze the change of dimethylarginine plasma levels in cirrhotic patients receiving transjugular intrahepatic portosystemic shunt (TIPS). METHODS: To determine arginine, asymmetric dimethylarginine (ADMA), symmetric dimethylarginine (SDMA), and nitric oxide (NO) plasma levels, blood samples were collected from the superior cava, hepatic, and portal vein just before, directly after, and 3 mo after TIPS-placement. RESULTS: A significant increase in the arginine/ADMA ratio after TIPS placement was shown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
(40 reference statements)
2
12
0
Order By: Relevance
“…Similar to prior published experience, there was no significant change in ADMA levels after TIPS placement in the entire group[21]. We also did not find a difference in the baseline ADMA levels between those who did or did not develop HE ultimately.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to prior published experience, there was no significant change in ADMA levels after TIPS placement in the entire group[21]. We also did not find a difference in the baseline ADMA levels between those who did or did not develop HE ultimately.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have shown that ADMA levels are increased in plasma of patients with severe acute alcoholic hepatitis and ALF (Mookerjee et al, 2007a(Mookerjee et al, , 2007b. Recent evidence indicates that the l-arginine/ ADMA ratio in plasma is increased in cirrhotic patients with transjugular intrahepatic portosystemic shunt (TIPS) (Bajaj et al, 2013;Siroen et al, 2008), which implicates an increase in intracellular NO bioavailability. Moreover, higher ADMA concentration is related to worsened outcome of cognition tests in TIPS patients and predict the transition from asymptomatic to overt HE (Bajaj et al, 2013).…”
Section: Article In Pressmentioning
confidence: 98%
“…Siroen et al . 17 demonstrated a significant negative correlation between SDMA levels and creatinine clearance in patients with alcoholic cirrhosis undergoing transjugular intrahepatic porto-systemic shunt placement (P<0.001). Lluch et al .…”
Section: Introductionmentioning
confidence: 94%
“…20 showed that (SDMA+ADMA) was significantly elevated in patients with acute alcoholic hepatitis plus cirrhosis compared to those who had cirrhosis alone. The results of these two studies in subjects with cirrhosis suggested that dimethylarginines might be a useful GFR marker in cirrhosis 1720 .…”
Section: Introductionmentioning
confidence: 96%